CRM Systems Quality Evaluation - Boarim, Jhonatan Bernardes; da Rocha, Ana Regina Cavalcanti (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2021)
Companies need to manage the expectations and relationship with their clients. Customer relationship management (CRM) systems provide tools to support these tasks. Evaluating and selecting a CRM system is not a trivial task. This work identified the important quality characteristics and sub-characteristics for CRM systems in a Literature Systematic Mapping, comparing results obtained with the software quality models from ISO/IEC 25010 standard and conducting a survey in the Brazilian CRM systems industry. Finally, an available CRM on the market was evaluated to verify the feasibility of evaluating CRM products using the set of identified characteristics.